Pelaksanaan asuhan gizi terapi gizi medis (TGM) berpengaruh terhadap lama rawat inap - Ika Yuliati Chasbullah; I Made Alit Gunawan; R Dwi Budiningsari (Jurnal Gizi Klinik Indonesia, 2011)
Background: Medical Nutrition Therapy (MNT) is one of nutrition care models which focuses on integrated patient management involving active participation of doctors, nutritionists, nurses and other professions within the hospital nutrition care team. One benefit of MNT is the reducing of patients’ length of stay (LOS) as an indicator of hospital service quality. Bekasi Municipal Hospital has not implemented integrated nutrition care within a team. The result of monitoring and evaluation during the frst quarter of 2006 showed the average of LOS for degenerative diseases patients was 5.97 days.Objective: To identify the influence of nutrition care implementation by using MNT approach to LOS at Bekasi Municipal Hospital.Method: The study was quaci-experimental which uses static-group comparison. Samples were patients hospitalized at internal medicine wards of (class) VIP, 1 , 2  and 3  class. Datas were obtained consisted of conventional nutrition standard care (CNC), MNT, and data of LOS. T-test and Mann Whitney statistical test were used to analyze the influence of types of nutrition care to LOS.Results: LOS of patients with MNT care was 5.80 days. This was shorter than CNC and statistically significant (p<0.05).Conclusion: There was a difference between LOS of samples with MNT and CNC. LOS of samples with MNT was shorter than CNC and statistically significant (p<0.05).